PENGARUH HARGA, DESAIN DAN LOKASI TERHADAP KEPUTUSAN PEMBELIAN SERTA DAMPAKNYA PADA KEPUASAN PASCA PEMBELIAN PERUMAHAN DI KOTA BANDA ACEH - Fachrul Rizal; Muhammad Adam; Mahdani Ibrahim (Jurnal Manajemen Inovasi, 2017)
ABSTRACT The aim of this research is to know (1) satisfaction of post purchase, purchasing decision, price, design, and residential location in Banda Aceh City, (2) influence of price, design and location, either simultantly or partially to decision of purchase of housing (3) The effect of price, design and location, either simultantly or partially on the satisfaction of post-purchase housing (4) the effect of purchasing decisions on satisfaction of post-purchase housing, (5) to analyze whether purchasing decisions mediate price, design and location influence on post- City of Banda Aceh. This research was conducted in Banda Aceh City, with the object of research is purchasing decision and post-purchase satisfaction is price, design and location with the number of respondents as many as 100 people. The results of this study indicate that the respondents have good perception of price variables, design, location, purchase decision and post-purchase satisfaction of housing in Banda Aceh City, this is because the average value for all research variables is greater than 4 in likert scale. The result of the research shows that the price, design, location both simultaneously and partially influence the decision of purchase of housing and price, design and location both simultaneously and partially influence to satisfaction of post-purchase of housing in Banda Aceh City, and also purchasing decision have influence to post- Purchase of housing in Banda Aceh City. Then the research also proves that there is indirect influence of price, design and location to the satisfaction of post-purchase of housing in Banda Aceh City. Through purchasing decisions. Keywords:       Post Purchase Satisfaction, Purchase Decision, Price, Design, and Location